1996
DOI: 10.1016/0014-5793(96)00219-0
|View full text |Cite
|
Sign up to set email alerts
|

Yeast aspartic protease 3 (Yap3) prefers substrates with basic residues in the P2, P1 and P2′ positions

Abstract: The yeast aspartic protease Yap3 is localised to the secretory pathway and correctly cleaves pro-a-mating factor at its dibasic sites. We determined the specificity of Yap3 for mono-, di-and multi-basic cleavage sites in the context of 15 residue synthetic proalbumin peptides. Yap3 cleaved after dibasic ArgArg and LysArg sites but not after monobasic Arg sites even when there was an additional arginine at -6 and/or -4. Yap3 did not cleave a tetra-arginine site and tribasic sites (RRR and RRK) were poor substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 23 publications
3
19
0
Order By: Relevance
“…Extensive analyses of its specificity (15,(22)(23)(24) have revealed that substrates containing multiple basic residues surrounding the scissile bond are cleaved with high efficiencies. The nature of this specificity is not completely understood even though molecular modeling (Protein Data Bank code 1YPS) (24) has revealed that yapsin 1 has a more open active site compared with other aspartyl proteases and that many of its subsites are electronegative, thus allowing for the accommodation of positively charged residues within and surrounding the cleavage site (24).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive analyses of its specificity (15,(22)(23)(24) have revealed that substrates containing multiple basic residues surrounding the scissile bond are cleaved with high efficiencies. The nature of this specificity is not completely understood even though molecular modeling (Protein Data Bank code 1YPS) (24) has revealed that yapsin 1 has a more open active site compared with other aspartyl proteases and that many of its subsites are electronegative, thus allowing for the accommodation of positively charged residues within and surrounding the cleavage site (24).…”
Section: Discussionmentioning
confidence: 99%
“…In the same expression system, yapsin 1 activity was also found in the culture supernatant and was characterized as ϳ150 -180-and ϳ90-kDa hyperglycosylated forms that appeared to be highly stable (8). Ϫ1 for human adrenocorticotropin (ACTH ) (15), demonstrating an enhancement of the efficiency by additional basic residues upstream and especially downstream of the cleavage site (15,16).…”
mentioning
confidence: 89%
“…The intermediate form undergoes a further intermolecular or intramolecular cleavage of the remainder of the proregion to generate the mature active enzyme. It is interesting to note the similarity to yapsin 1 in this respect in that a potential cleavage site exists at Lys 16 -Phe 17 within the propeptide. Because of this structural similarity and that cleavage of a mono-lysine residue by yapsin 1 has previously been documented (15), it is predicted that a yapsin 1 intermediate, formed from an intramolecular cleavage presumably at this site, exists.…”
Section: Fig 7 Proyapsin 1 Was Incubated For 22 H At Ph 72 and Ph mentioning
confidence: 99%
See 2 more Smart Citations